2010
DOI: 10.1007/s12028-010-9335-4
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Vasculopathy of Intracranial Large- and Medium-Sized Vessels in Neurological Intensive Care Unit: A Clinico-Radiological Study

Abstract: In this cohort, one-third of all cases of nonatherosclerotic vasculopathy were due to infectious vasculopathy of large and medium intracranial vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 40 publications
2
14
2
2
Order By: Relevance
“…Occlusion of the MCA with development of moyamoya collaterals has been reported in children (20). Vessel wall thickening and contrast-enhanced vessel walls on imaging have been seen in VZV vasculopathy (21). In 5/6 patients with virologically-verified VZV vasculopathy confirmed by the presence of anti-VZV IgG antibody in CSF, vessel wall enhancement on highresolution MRI resolved and arterial stenosis improved or stabilized after treatment with intravenous acyclovir (22).…”
Section: Clinical Laboratory and Imaging Features Of Vzv Vasculopathymentioning
confidence: 99%
“…Occlusion of the MCA with development of moyamoya collaterals has been reported in children (20). Vessel wall thickening and contrast-enhanced vessel walls on imaging have been seen in VZV vasculopathy (21). In 5/6 patients with virologically-verified VZV vasculopathy confirmed by the presence of anti-VZV IgG antibody in CSF, vessel wall enhancement on highresolution MRI resolved and arterial stenosis improved or stabilized after treatment with intravenous acyclovir (22).…”
Section: Clinical Laboratory and Imaging Features Of Vzv Vasculopathymentioning
confidence: 99%
“…While treatment reduces further stroke [4], the course of resolution of vessel inflammation and stenosis is unknown. Recent studies using contrast-enhanced vessel wall imaging high-resolution MRI (HRMR) showed that vessel wall thickening and enhancement correlate with vessel wall inflammation in central nervous system vasculitis [5], including VZV vasculopathy [6,7], however, data on follow up imaging after treatment has not been previously published. Knowledge of the extent and evolution of vessel wall enhancement, which likely reflects inflammation, may help to guide treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study on infectious CNS vasculitis, magnetic resonance angiography was shown to detect vasculopathic signs in all 8 patients. 12 In our case, TOF angiography with a 3 T scanner was sufficient to visualize alterations in large to medium-sized arteries. Contrast-enhanced T1-weighted images may be even more sensitive by detection of vessel wall enhancement, particularly if medium to small vessels are affected.…”
Section: Oystersmentioning
confidence: 60%